Case Report: Response to Intra-arterial Cisplatin and Concurrent Radiotherapy Followed by Salvage Surgery in a Patient With Advanced Primary Sinonasal Low-Grade Non-intestinal Adenocarcinoma - Tachino, Hirohiko; Takakura, Hiromasa; Shojaku, Hideo; Fujisaka, Michiro; Akaogi, Katsuichi; Kawabe, Hideto; Naruto, Norihito; Shojaku, Hiroko; Noguchi, Kyo; Miwa, Shigeharu; Imura, Johji; Maeda, Yoshinobu (Frontiers in Surgery, 2020)
Background. The clinical usefulness of concurrent chemoradiotherapy before surgery in the treatment of primary, locally advanced sinonasal low-grade, non-intestinal type adenocarcinoma (LG non-ITAC) is unclear. Methods. We present the first case report of the efficacy of super-selective intra-arterial cisplatin (CDDP) infusion concurrent with conventional fractionated radiotherapy (RT) for LG non-ITAC in a Japanese patient. Results. A white, rugged-marginal mass that was histopathologically diagnosed as LG non-ITAC occupied the right nasal cavity. Based on the imaging findings, including computed tomography, magnetic resonance imaging and positron emission tomography, the tumor was diagnosed as T4aN0M0, stage IVa. After treatment, the nasal tumor disappeared leaving only a small bulge in the medial wall of the middle turbinate. The patient also underwent right transnasal ethmoidectomy performed as salvage surgery. A histopathological examination revealed that the lesion was replaced by granulation tissue with lymphocytic infiltration and hemosiderin-laden macrophages, and no viable tumor cells remained. In the seven years after treatment, the patient has not experienced any local recurrence or regional or distant metastasis. Conclusions. Super-selective intra-arterial CDDP infusion concurrent with conventional fractionated RT followed by salvage surgery might be useful for the management of sinonasal LG non-ITAC.